Association of folic acid dosage with circulating unmetabolized folic acid in Chinese adults with H-type hypertension: a multicenter, double-blind, randomized controlled trial - Chen, Ping; Tang, Linlin; Song, Yun; Wang, Binyan; Qin, Xianhui; Zhang, Nan; Wei, Yaping; Xu, Xiping; Zhou, Ziyi; He, Qiangqiang; Liu, Lishun; Siddiqi, Sultan Mehmood; et al. (Frontiers in Nutrition, 2023)
Background: There is growing concern regarding elevated levels of circulating unmetabolized folic acid (UMFA) due to excessive intake of folic acid (FA). However, no randomized clinical trial has been conducted to examine the FA-UMFA dose-response relationship.Objective: This study aimed to investigate the FA-UMFA dose-response relationship in Chinese adults with hypertension and elevated homocysteine (H-type hypertension), a population with clear clinical indication for FA treatment.The data for this study were derived from a randomized, double-blind, multicenter clinical trial of 8 FA dosages on efficacy of homocysteine (Hcy) lowering. The parent trial had three 3 stages: screening period (2-10 days), run-in period (0-2 weeks, baseline visit), and double-blind treatment period (8 weeks) with follow-up visits at the end of the 2 nd , 4 th , 6 th , and 8 th weeks of treatment.Participants were randomly assigned to 8 treatment groups corresponding to FA dosages of 0, 0.4, 0.6, 0.8, 1.2, 1.6, 2.0 mg to 2.4 mg.Results: This study included 1,567 Chinese adults aged ≥45 years with H-type hypertension. There was a positive but non-linear association between FA supplementation and UMFA levels in the dosage range of 0 mg to 2.4 mg. In the regression analysis, the coefficients for the linear and quadratic terms of FA dosage were both statistically significant (P <0.001). Notably, the slope for UMFA was greater for FA dosages >0.8 mg (ß =11.21, 95% CI: 8.97, 13.45) compared to FA dosages ≤0.8 mg (ß = 2.94, 95% CI: 2.59, 3.29). Furthermore, FA dosages higher than 0.8 mg did not confer additional benefits in terms of increasing 5-methyl tetrahydrofolic acid (5-MTHF, active form of folate) or reducing homocysteine (Hcy).In Chinese adults with H-type hypertension, this study showed a positive, non-linear, dosage-response relationship between FA supplementation ranging from 0 mg to 2.4 mg and circulating UMFA levels. It revealed that 0.8 mg FA is an optimal dosage in terms of balancing efficacy (increasing 5-MTHF and lowering Hcy) while minimizing undesirable elevation of UMFA.